Analisis Persepsi Petani Terhadap Pemanfaatan Irigasi Pada Usahatani Padi di Sub DAS Krueng Jreu - Ainal; Lolita; Meliyana (LPPM Universitas Malikussaleh - Indonesia, 2026)
Irrigation is an important factor in supporting the sustainability of paddy rice farming, especially in areas that depend on surface water sources. A well-functioning irrigation system not only ensures the availability of water for plants, but also affects the smooth cultivation of crops, yield stability, and the sustainability of farming. This study aims to analyze farmers' perceptions of irrigation utilization and identify factors that affect it in the Krueng Jreu Sub Watershed, Aceh Besar Regency. The study used a survey method of 40 paddy farmers selected by simple random sampling. Data were collected through questionnaires and analyzed using the Likert scale and multiple linear regression. The results of the study show that farmers' perception of irrigation utilization is in the good category. This can be seen from the average score of water availability 3.75, water distribution 3.90, system reliability 3.86, economic benefits 4.02, participation and institutions 3.83, and infrastructure maintenance 3.98. The regression results showed that all independent variables simultaneously affected farmers' perceptions with the model's ability to explain 47% of the perception variation. Partially, there are no variables that have a significant influence, but infrastructure maintenance is the most dominant factor. These findings affirm the importance of improving infrastructure, equitable water distribution and strengthening farmer institutions.